Are Clinical Impairments Related to Kinematic Gait Variability in Children and Young Adults With Cerebral Palsy? - Tabard-Fougère, Anne; Rutz, Dionys; Pouliot-Laforte, Annie; De Coulon, Geraldo; Newman, Christopher J.; Armand, Stéphane; Wegrzyk, Jennifer (Frontiers in Human Neuroscience, 2022)
Intrinsic gait variability (GV), i.e. fluctuations in the regularity of gait patterns between repetitive cycles, is inherent to the sensorimotor system and influenced by factors such as age and pathology. Increased GV is associated with gait impairments in cerebal palsy (CP) and has been mainly studied based on spatiotemporal parameters. The present study aimed to describe kinematic GV in CP and its associations with clinical impairments (i.e. passive range of motion (pROM), muscle weakness, reduced selective motor control (selectivity) and spasticity). This retrospective study included 177 participants with CP (age range 5-25 yrs; Gross Motor Function Classifcation System I-III) representing 289 clinical gait analyses. Root Mean Square Deviation (RMSD) for nine lower-limb kinematic parameters and Gait Standard Deviation (GaitSD) were computed for the affected (unilateral = uCP) and most affected side (bilateral = bCP) respectively, as defined by clinical scores. GaitSD was then computed for the non/less-affected side for between leg comparisons. Uni- and multivariate linear regressions were performed on GaitSD with all clinical impairments (composite scores) as independent variables. Highest RMSD were found in the transverse plane (hip, pelvis), for distal joints in the sagittal plane (knee, ankle) and for foot progression. GaitSD was not different between uCP and bCP (affected / most affected side) but higher in the non-affected vs. affected side in uCP. GaitSD was associated with age (p<0.001), gait deviation index (GDI) (p<0.05), muscle weakness (p<0.001), selectivity (p<0.05) and pROM (p<0.001). After adjustment for age and GDI, GaitSD remained associated with muscle weakness (uCP: p=0.003, bCP: p<0.001) and selectivity (bCP: p=0.024). Kinematic GV can be expressed as global indicator of variability (GaitSD) in youngsters with CP given the strong correlation of RMSD for lower-limb kinematic parameters. In terms of asymmetry, increased variability of the non-affected vs affected side may indicate contralateral compensation mechanisms in uCP. Notably muscle weakness (uCP, bCP) and selectivity (bCP) - but not spasticity - were associated with GaitSD. Further studies need to explore the clinical relevance of kinematic GV in CP to support the interpretation of clinical gait analyses and therapeutic decision-making.